EFFECT OF LIFESTYLE MODIFICATION IN TYPE II DIABETES MELLITUS INDIVIDUALS - BHOSALE, AVANI; THANGAVELU, POOVISHNU DEVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objectives of this study were as follows: (1) To find the effect of conventional physiotherapy along with medications on Type II diabetes mellitus (DM) individuals and (2) to find the effect of lifestyle modification (LSM) and conventional physiotherapy with medications on Type II DM individuals. Methods: Ethical clearance was obtained from the institutional ethical committee. A total of 70 Type II DM individuals were assessed and 64 were included in this study based on inclusion criteria, the individuals were allocated into two groups: Group A (n=32) received conventional physiotherapy along with prescribed diabetic medications and Group B (n=32) received LSM and conventional physiotherapy with prescribed diabetic medications. Pre- and post-test were done for plasma glucose, serum insulin, glycated hemoglobin (HbA1c), total cholesterol, triglycerides, high-density lipoprotein-C, low-density lipoprotein by blood test, exercise tolerance by 6-min walk test, and quality of life (QOL) by SF-36 questionnaire, and the outcome measures were analyzed after 3 months. Results: Intergroup statistical analysis for HbA1c (p<0.0001) and QOL (p<0.0001) revealed extremely significant difference post-intervention. Analysis of HbA1c test for Group A (p=0.0652) was not significant and for Group B (p<0.0001) was extremely significant. Moreover, QOL was significant for Group A (p=0.0004) as well as for Group B (p<0.0001). Conclusion: The study results concluded that LSM was significantly effective in reducing HbA1c levels, exercise tolerance, plasma glucose, serum glycerine, and total cholesterol and improving QOL compared to conventional exercise.